2004
DOI: 10.1200/jco.2004.04.132
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Guidelines for the Treatment of Cancer Treatment-Induced Diarrhea

Abstract: With vigilant monitoring and aggressive therapy for cancer treatment-induced diarrhea, particularly in patients with early warning signs of severe complications, morbidity and mortality may be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
438
0
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(467 citation statements)
references
References 33 publications
7
438
0
18
Order By: Relevance
“…Administration of this drug, however, causes 2 forms of diarrhea, an early cholinergic diarrhea and a severe delayed diarrhea, both of which are distressing to patients and can cause disruptions in treatment. 4,5 Previous research has proposed varying mechanisms for the delayed-onset diarrhea, [6][7][8][9] but the definitive mechanism behind this remains unknown. It has been previously shown that irinotecan differs from most cytotoxic agents in that it causes severe gastrointestinal damage with increased apoptosis in both the small and large intestines, changes in intestinal morphometry and excessive mucus secretion in the colon.…”
mentioning
confidence: 99%
“…Administration of this drug, however, causes 2 forms of diarrhea, an early cholinergic diarrhea and a severe delayed diarrhea, both of which are distressing to patients and can cause disruptions in treatment. 4,5 Previous research has proposed varying mechanisms for the delayed-onset diarrhea, [6][7][8][9] but the definitive mechanism behind this remains unknown. It has been previously shown that irinotecan differs from most cytotoxic agents in that it causes severe gastrointestinal damage with increased apoptosis in both the small and large intestines, changes in intestinal morphometry and excessive mucus secretion in the colon.…”
mentioning
confidence: 99%
“…Most drug toxicity can be managed with appropriate use of urea based creams and topical emollients, antiemetics, and antidiarrhea medication. 27,28 Efficacy should be documented with imaging. Computed tomography or magnetic resonance imaging of the chest, abdomen, and pelvis to include areas of active disease should be performed at regular intervals.…”
Section: Monitoring Of Therapymentioning
confidence: 99%
“…In general, Child-Pugh B patients treated with sorafenib do not live as long as patients with Child-Pugh A, but Table adapted from sorafenib package insert for managing skin toxicities. Treatment strategies for managing skin toxicity and diarrhea can be found in Lacouture et al 27 and Benson et al, 28 respectively. that could very well reflect the natural history of their liver disease rather than a difference in anticancer activity of sorafenib.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%
“…In vitro studies have shown that telmisartan acts as a partial agonist of PPARg and modulates the expressions of PPARg target genes involved in carbohydrate and lipid metabolism. 16 One report suggests that telmisartan, in contrast to some other ARBs, may exert additional effects through activation of PPARg. 17 Telmisartan induces adiponectin expression via PPARg activation 18 and proliferates human endothelial progenitor cells via a PPARg-dependent PI3K/Akt signaling pathway.…”
Section: Introductionmentioning
confidence: 99%